2007
DOI: 10.1063/1.2825419
|View full text |Cite
|
Sign up to set email alerts
|

Nonpolar m-plane thin film GaN and InGaN∕GaN light-emitting diodes on LiAlO2(100) substrates

Abstract: The nonpolar m-plane ͑1100͒ thin film GaN and InGaN / GaN light-emitting diodes ͑LEDs͒ grown by metal-organic chemical vapor deposition on LiAlO 2 ͑100͒ substrates are reported. The LEDs emit green light with output power of 80 W under a direct current of 20 mA for a 400 ϫ 400 m 2 device. The current versus voltage ͑I-V͒ characteristic of the diode shows soft rectifying properties caused by defects and impurities in the p-n junction. The electroluminescence peak wavelength dependence on injection current, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
34
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 21 publications
0
34
0
Order By: Relevance
“…It also exhibits some collinear features in the GaN epilayer probed by atomic force microscopy. 4 Both anisotropic crystallography and surface morphology are quite similar to the behavior of nonpolar GaN grown on different substrates. 5,8,16 This result implies different mosaic block dimensions along the two orthogonal directions, parallel and perpendicular to the ͓0001͔ direction of m-plane GaN.…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…It also exhibits some collinear features in the GaN epilayer probed by atomic force microscopy. 4 Both anisotropic crystallography and surface morphology are quite similar to the behavior of nonpolar GaN grown on different substrates. 5,8,16 This result implies different mosaic block dimensions along the two orthogonal directions, parallel and perpendicular to the ͓0001͔ direction of m-plane GaN.…”
mentioning
confidence: 52%
“…Consequently, it results in reduction of quantum efficiency of light-emitting diodes. 2 A way to overcome this deficiency is to grow GaNbased QWs along nonpolar orientations, for example, m plane 3,4 or a plane. 5,6 It has been shown that the electric field can be avoided in such nitride QWs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The m-plane InGaN/GaN multiple quantum wells (MQWs) have been synthesized substrates by molecular-beam epitaxy(MBE) 4 and LED structures have been grown by metal-organic chemical vapor deposition (MOCVD) on LiAlO 2 [LAO] (100) 5,6 , recently. This non-polar plane GaN will exhibit intrinsic in-plane anisotropy even in the unstrained case due to the broken hexagonal symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…4 High-resolution x-ray diffraction technique revealed the m-plane GaN epilayer under biaxial compressive strain of xx = −0.79% and zz = −0.14% with an out-of-plane dilatation yy = 0.38%. 15 An unintentionally doped n-type c-plane GaN with thickness of 2.5 m on ␣-Al 2 O 3 ͑0001͒ substrate ͑named as sample II͒ was used to compare the luminescence properties of m-plane GaN film.…”
mentioning
confidence: 99%